Implementasi Mesin Pengolah â€œOpak Gambirâ€ Guna Peningkatan Efisiensi Produksi - Wiwiek Kusumaning Kusumaning; Ellya Nurfarida; Mujahid Wahyu (JURNAL DAYA-MAS, 2019)
Opak Gambir, or better known as the "semprong cake" community, is one of the leading commodities in the City of Small and Medium Enterprises (IKM) of Kediri. This community service program is a processed business "Opak Gambir" which is made from tapioca flour which is one of the household industries in Kediri City. The purpose of this community service program is as an effort to overcome the problems faced by partners with the following stages: 1) Making a semi-automatic production machine does not need to flip through the Opak Gambir dough and there are many molds in the machine. At present the production that is carried out still uses manual labor so that in producing it is still less efficient it requires a long time and a lot of costs, 2) Providing training and assistance to find out the efficiency of the production used. The result of this service program was to produce a semi-automatic Opak Gambir machine with an electric dynamo for production efficiency so that the business would get optimal profits.Â Keywordsâ€”: Production Machines; Opak Gambir; Production Efficiency.